Quartiers anciens dédiés au tourisme et aux loisirs en Chine. Pratiques et représentations des usagers de NanTangLaoJie à Ningbo - Annie Ouellet (Belgeo)
This paper explores the question of the transformations of old districts in China. The contribution focuses on the practices and representations of users of NanTangLaoJie, a district of Ningbo, a city located on the east coast of China. This district is emblematic of the situation of many old Chinese districts: an area from which the permanent residents have been evicted, which has been completely restored, even rebuilt and which is now dedicated to tourism and leisure. Structured interviews conducted with users of the district allow to highlight similar practices (walking around, taking pictures, eating, shopping) regardless of the category of individuals involved. Interviews also make it possible to identify contrasting representations of heritage.